Energy Consumption of an Active Vehicle Suspension with an Optimal Controller in the Presence of Sinusoidal Excitations - Jarosław Konieczny; Waldemar Rączka; Marek Sibielak; Janusz Kowal (Shock and Vibration, 2020)
Control of vibration is a significant problem in the design and construction of vehicle suspensions. The usage of controlled suspensions is important due to ride comfort, driving safety, and vehicle road holding. The control law for such systems is usually determined as a solution of an optimisation problem with a quality indicator. The effectiveness of vibration reduction is possible to be improved in the entire useful frequency range of a system operation, but usually increasing external energy consumption is observed. An additional problem in the case of vehicle suspensions includes the necessity for increased vibration reduction at selected frequencies. This is related to the natural frequencies of the driver’s internal organs or to other reasons. The goal of this work is to find a compromise between efficiency of the suspension in terms of the aforementioned indicators and energy consumption in the presence of sinusoidal excitations. This paper presents a synthesis of a weighted multitone optimal controller (WMOC) for an active vibration reduction system. Energy limitation is taken into account by selection coefficients of the weighting matrix associated with the control signal vector. The control signal in this case is determined on the basis of the parameter estimation of the sinusoidal disturbances vector (PESDV). The vibration transmissibility function and the energetic indicators for the active suspension were determined while taking note of nonlinearities occurring in the actual vehicle. The analysis of energy indicators is presented, depending on the level of vibration reduction efficiency. The results were compared with referencing to LQR control strategy.